A hospital based study of scenerio of glaucoma patients in upper Assam, India - Gogoi, T.; Bhattacharjee, Supantha (International Journal of Research in Medical Sciences, 2017)
Background: Glaucoma can be defined as a chronic multifactorial optic neuropathy with a characteristic accelerated degeneration of retinal ganglion cells presenting as classical optic nerve head features and correlating visual field changes, which may or may not be associated with angle abnormality in the presence or absence of any cause for the disease. Methods: This was a prospective hospital based study of patients >40years with a suspicion of glaucoma attending the Outpatient Department of Ophthalmology, Assam Medical College, Dibrugarh, Assam, india. Patients were subjected to a comprehensive eye examination to diagnose and classify glaucoma. Results: In this study out of 1000 patients, 22 were diagnosed to have glaucoma (2.2%), most common age group >61years (50%), male patients were 73%, PACG accounted for 11 patients (50%). POAG in 7 cases (32%), LIG in 14%, Neovuscular in 1 cases (5%). Conclusions: Glaucoma prevalence, age and sex distribution was found to be similar to studies conducted in other parts of India. Most common type of glaucoma was PACG followed by POAG.